Non Metallic Anterior Chamber Foreign Body: A Case Report - Afifah, Nabilah; Nina Handayani; Triana Budi Sulistya (Majalah Oftalmologi Indonesia, 2025)
Introduction: Intraocular foreign body (IOFB) is a serious form of open-globe injury that can cause a serious ocular trauma that lead to blindness (10–40% of all open eye injuries). This case report is aimed to report a challenging management of anterior chamber foreign body. Case Report: A 41 year-old man presented with discomfort on his right eye 4 days prior to visit. The slit lamp biomicroscopic examination revealed inferior anterior chamber foreign body (stone), measuring 5 x 2 mm and 5 mm scar at the area of a full thickness self-sealed corneal laceration. The corneal edema was localized hence it was possible to visualize the foreign body’s entire path through the cornea. The foreign body was removed with forceps from superior limbal incision. Post operative visual acuity was improved and the inflammation was decreased. Discussion: Management of such cases is not always easy because certain ACFB made of inert materials (stone, plastic, glass, and inert metals such as gold, silver, or platinum) excite minimal inflammation and may remain quiescent for a long period of time. An anterior IOFB is usually associated with a better final BCVA than a posterior IOFB. The self-sealing wounds were limited to the paracentral or peripheral cornea, resulting in no significant astigmatism. Conclusion: The risk of intraocular foreign body is associated with mechanism of injury and history taking must be accurate. Intraocular foreign bodies must have surgical removal to prevent of ocular inflammation and complication. Keywords: Anterior Chamber Foreign Bodies (ACFB), IOFB, Open Globe Injury, Penetrating Injury